Second Harmonic Generation Imaging of Collagen in Chronically Implantable Electrodes in Brain Tissue - Esquibel, Corinne R.; Wendt, Kristy D.; Lee, Heui C.; Gaire, Janak; Shoffstall, Andrew; Urdaneta, Morgan E.; Chacko, Jenu V.; Brodnick, Sarah K.; Otto, Kevin J.; Capadona, Jeffrey R.; Williams, Justin C.; Eliceiri, K. W. (Frontiers in Neuroscience, 2020)
Advances in neural engineering have brought about a number of implantable devices for improved brain stimulation and recording. Unfortunately, many of these micro-implants have not been adopted due to issues of signal loss, deterioration, and host response to the device. In the search for a chronically useful and reliable neural interface, it is important to examine the tissue environment around implanted devices to see what response might occur that would either affect the device’s functionality or tissue viability. While characterization of the brain wounding response known as glial scars typically involves immunohistochemical labeling, the corresponding tissue processing and sectioning frequently result in device shattering and tissue tearing artifacts that prevent analysis of the glial scar. In this methods implementation study, we use the label free, optical sectioning method of second harmonic generation (SHG) to examine brain slices of various implanted intracortical electrodes and demonstrate collagen fiber patterns not found in normal brain tissue. SHG can easily be used in conjunction with multiphoton microscopy to allow direct intrinsic visualization of collagen-containing glial scars on the surface of cortically implanted electrode probes without imposing the physical strain of tissue sectioning methods required for other high resolution light microscopy modalities. Identification and future measurements of these collagen fibers may be useful in predicting host immune response and device signal fidelity.